At large and at small familiar essays - Fadiman, Anne 1953- (Farrar, Straus and Giroux, 2008)
"In At Large and At Small, Anne Fadiman returns to one of her favorite genres, the familiar essay - a beloved literary tradition recognized for both its intellectual breadth ("at large") and its miniaturist focus ("at small"). With the combination of humor and erudition that has distinguished her as one of our finest essayists, Fadiman draws us into twelve of her personal obsessions, ranging from her slightly sinister childhood enthusiasm for catching butterflies to her monumental crush on Charles Lamb, from her wistfulness for the days of letter-writing to the challenges and rewards of moving from the city to the country."--Book jacket.